2016
DOI: 10.7717/peerj.2398
|View full text |Cite
|
Sign up to set email alerts
|

Patchiness of forest landscape can predict species distribution better than abundance: the case of a forest-dwelling passerine, the short-toed treecreeper, in central Italy

Abstract: Environmental heterogeneity affects not only the distribution of a species but also its local abundance. High heterogeneity due to habitat alteration and fragmentation can influence the realized niche of a species, lowering habitat suitability as well as reducing local abundance. We investigate whether a relationship exists between habitat suitability and abundance and whether both are affected by fragmentation. Our aim was to assess the predictive power of such a relationship to derive advice for environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 111 publications
(140 reference statements)
0
16
0
Order By: Relevance
“…In the past two decades, advancements in statistical methods have promoted the development of SDMs, and numerous statistical methods and software programs have been developed to describe the niche characteristics of species and predict species distribution patterns. The popular algorithms are as follows: surface range envelope (SRE, i.e., BIOCLIM) (Booth, Nix, Busby, & Hutchinson, 2014), flexible discriminant analysis (FDA) (Basile et al, 2016), generalized linear model (GLM) (Lopatin, Dolos, Hernández, Galleguillos, & Fassnacht, 2016), generalized additive model (GAM) (Muñoz-Mas, Papadaki, Martinez-Capel, Zogaris, & Ntoanidis, 2016), multiple adaptive regression splines (MARS) (Friedman, 1991), generalized boosting model (GBM) (Moisen et al, 2006), classification tree analysis (CTA) (Thuiller & Lavorel, 2010), artificial neural network (ANN) (Segurado & Araujo, 2004), random forest (RF) (Mi, Huettmann, Guo, Han, & Wen, 2017), and maximum entropy (MaxEnt) (Phillips, Anderson, & Schapire, 2006). However, differential niche requirements of species shape the geographic distribution of species within an environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, advancements in statistical methods have promoted the development of SDMs, and numerous statistical methods and software programs have been developed to describe the niche characteristics of species and predict species distribution patterns. The popular algorithms are as follows: surface range envelope (SRE, i.e., BIOCLIM) (Booth, Nix, Busby, & Hutchinson, 2014), flexible discriminant analysis (FDA) (Basile et al, 2016), generalized linear model (GLM) (Lopatin, Dolos, Hernández, Galleguillos, & Fassnacht, 2016), generalized additive model (GAM) (Muñoz-Mas, Papadaki, Martinez-Capel, Zogaris, & Ntoanidis, 2016), multiple adaptive regression splines (MARS) (Friedman, 1991), generalized boosting model (GBM) (Moisen et al, 2006), classification tree analysis (CTA) (Thuiller & Lavorel, 2010), artificial neural network (ANN) (Segurado & Araujo, 2004), random forest (RF) (Mi, Huettmann, Guo, Han, & Wen, 2017), and maximum entropy (MaxEnt) (Phillips, Anderson, & Schapire, 2006). However, differential niche requirements of species shape the geographic distribution of species within an environment.…”
Section: Introductionmentioning
confidence: 99%
“…Birds are frequently reported as the most practical biodiversity indicators, namely at larger scales [25,57,58] and are particularly relevant to assess habitat fragmentation [73][74][75][76]. However, birds are more suitable indicators of habitat structure than habitat species composition [77], since its abundance and richness is mainly correlated with forest structure and less with tree species composition [78][79][80].…”
Section: Forest Species Compositionmentioning
confidence: 99%
“…Studies aimed at predicting species abundance from species occurrence distribution models have yielded mixed results (e.g., Conlisk et al, 2009;Jiménez-Valverde et al, 2009;Yañez-Arenas et al, 2014;Carrascal et al, 2015;Basile et al, 2016). A recent meta-analysis (Weber et al, 2016) concluded that occurrence data can be a reasonable proxy for abundance, especially if local environmental variables are considered when dealing with the abundancesuitability relationship.…”
Section: Relationship Between Local Abundance and Predicted Habitat Smentioning
confidence: 99%
“…4 and Figure S2). This is a concern as woodland specialists usually require large patches of continuous well-preserved forests (e.g., Santos, et al, 2002;Fahrig, 2003;Devictor et al, 2008), and habitat fragmentation negatively affects the abundance and suitability of an area for birds (e.g., Basile et al, 2016). Nonetheless, Tamadaba should be considered as a potential area for translocations of blue chaffinches, especially those sectors located at higher altitudes, with tall pine trees and higher summer rainfall.…”
Section: Habitat Suitability Outside the Main Distribution Areamentioning
confidence: 99%